2016
DOI: 10.1186/s12882-016-0394-4
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-lymphocyte ratio is associated with arterial stiffness in patients with peritoneal dialysis

Abstract: BackgroundPatients with peritoneal dialysis are in the persistent inflammation state and have elevated arterial stiffness. Neutrophil-lymphocyte ratio(NLR) is a new inflammatory marker in renal and cardiac disorders. Brachial-ankle pulse wave velocity (baPWV) is a non-invasive measurement, which is widely used as a surrogate marker of arterial stiffness. However, there is little evidence to show an association between NLR and baPWV in patients with peritoneal dialysis. The aim of this cross-section study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 26 publications
(27 reference statements)
2
23
0
Order By: Relevance
“…PD patients are at 5-to 10-fold higher risk for developing CVD than the age-matched general population [4]. Among PD patients, CVD is the main complication and major cause of death, accounting for nearly 60% of all-cause deaths [1]. However, this excessive CVD mortality is unlikely to be fully accounted for by traditional Framingham risk factors (age, male sex, diabetes, hypertension, hyperlipidemia, and smoking) because advances in relevant treatment fail to improve CVD risk significantly in ESRD patients [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD patients are at 5-to 10-fold higher risk for developing CVD than the age-matched general population [4]. Among PD patients, CVD is the main complication and major cause of death, accounting for nearly 60% of all-cause deaths [1]. However, this excessive CVD mortality is unlikely to be fully accounted for by traditional Framingham risk factors (age, male sex, diabetes, hypertension, hyperlipidemia, and smoking) because advances in relevant treatment fail to improve CVD risk significantly in ESRD patients [3].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is a severe complication of peritoneal dialysis (PD) and is to blame for nearly 60% of all-cause deaths in this population [1]. The high CVD mortality is not entirely explained by traditional cardiovascular risk factors [2].…”
Section: Introductionmentioning
confidence: 99%
“…Turkmen et al [5] also found that NLR could predict vascular calcification in patients with ESRD receiving peritoneal dialysis or hemodialysis. Recently, Cai et al [1] reported that NLR was independently associated with brachial-ankle pulse wave velocity (baPWV) in patients on peritoneal dialysis. But to date, little was known of the prognostic value of NLR in patients undergoing PD.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease is the main complication and major cause of death in patients undergoing peritoneal dialysis (PD), accounting for nearly 60% of all deaths in this population [1]. The high cardiovascular mortality associated with chronic renal disease, especially in patients with end-stage renal disease (ESRD), is not entirely explained by traditional cardiovascular risk factors [2].…”
Section: Introductionmentioning
confidence: 99%
“…Both NLR and AAC are associated with arterial stiffness, as neutrophil-to-lymphocyte ratio is independently associated with arterial stiffness in patients with advanced kidney disease, and aortic calcification is associated with arterial stiffness in the general population and hypertensive patients [28][29][30].…”
Section: Introductionmentioning
confidence: 99%